2001
DOI: 10.1038/sj.bjp.0704241
|View full text |Cite
|
Sign up to set email alerts
|

Dependency of detrusor contractions on calcium sensitization and calcium entry through LOE‐908‐sensitive channels

Abstract: 1 The subcellular mechanisms regulating stimulus-contraction coupling in detrusor remain to be determined. We used Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 67 publications
7
59
0
Order By: Relevance
“…donate (data not shown), consistent with observations using HEK-293 cells [32]. Several other non-voltage-activated Ca 2+ entry pathways that are distinct from SOC are also not inhibited by 2-APB, including maitotoxin-evoked Ca 2+ entry in hepatocytes [17], S-nitrosylation-induced influx in a smooth muscle cell line [33], Ca 2+ influx caused by diacylglycerol analogues in PC12 cells [34], muscarinic activation of non-selective cation channels in smooth muscle [35]. In many instances, 2-APB can be used to block SOC-mediated Ca 2+ influx, although it should be noted that it is not completely specific for SOC [10].…”
Section: Discussionsupporting
confidence: 74%
“…donate (data not shown), consistent with observations using HEK-293 cells [32]. Several other non-voltage-activated Ca 2+ entry pathways that are distinct from SOC are also not inhibited by 2-APB, including maitotoxin-evoked Ca 2+ entry in hepatocytes [17], S-nitrosylation-induced influx in a smooth muscle cell line [33], Ca 2+ influx caused by diacylglycerol analogues in PC12 cells [34], muscarinic activation of non-selective cation channels in smooth muscle [35]. In many instances, 2-APB can be used to block SOC-mediated Ca 2+ influx, although it should be noted that it is not completely specific for SOC [10].…”
Section: Discussionsupporting
confidence: 74%
“…The dependency of resting striated muscle stiffness on Ca 2ϩ is one reason that a portion of resting tension is attributed to cross bridges. In the present and previous studies (1, 46 -48), APS and the resulting passive tension in DSM are generated by contracting muscle strips at L s with KCl, carbachol, or PGE 2 in a Ca 2ϩ -containing solution, but then measured in tissues incubated for at least 2-5 min in a Ca 2ϩ -free solution, a duration sufficient to abolish a KClinduced contraction (22). An early study indicated that smooth muscle displays a resistance to stretch when tissues are bathed in a Ca 2ϩ -containing medium that is absent when tissues are bathed in a Ca 2ϩ -free solution (42).…”
Section: Discussionmentioning
confidence: 99%
“…To induce active contraction, tissues were stimulated by addition of KCl (PSS in which 110 mM KCl was substituted iso-osmotically for NaCl). Strips of rabbit DSM contract strongly to KCl in the presence of Ca 2ϩ , but incubation for only 2 min in a Ca 2ϩ -free solution prevents KCl from causing a contraction (22).…”
Section: Tissue Preparation and Mechanical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…15). In the urinary bladder, however, no direct evidence has been provided for cation channel activation by muscarinic receptor stimulation; although there have been some positive results from analysis of contractions, the contractile responses produced by muscarinic receptor stimulation were significantly inhibited by replacing extracellular Na + with impermeable NMDG + or by blocking non-selective cation channels after drug treatment (8,16). A patchclamp study in pig urinary bladder myocytes has shown that muscarinic receptor stimulation causes Ca…”
Section: +mentioning
confidence: 99%